2016
DOI: 10.1097/txd.0000000000000596
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic Hernia After Living Donor Right Hepatectomy: Proposal for a Screening Protocol

Abstract: BackgroundLiving donor hepatectomy (LDH) is increasingly being used to improve access to liver transplantation for those with end-stage liver disease. Although recipient outcomes are equivalent, donor complication rates range from 10% to 41%. A rare, but potentially serious complication is occurrence of a diaphragmatic hernia (DH), of which 9 cases have been reported so far in the literature. The purpose of this work was to review the clinical impact of DH post-LDH, including risk factors (RF) in hope of mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…The selected studies included 6 case reports, 6 9 11 14 16 17 4 retrospective case series, 4 7 8 12 2 letters to the editor, 10 15 and 2 original articles 13 18 ( Table 2 ). 4 6 7 8 9 10 11 12 13 14 15 16 17 18 Overall, 28 cases of DH after LR have been described (excluding our 3 cases). The most common indication of LR were as follows: living donor liver procurement in 11 cases (39.4%), liver metastases in 6 cases (21.4%), HCC in 2 cases (7.1%), adenoma in 2 cases (7.1%), focal nodular hyperplasia in one case (3.6%), and others in 6 cases (21.4%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies included 6 case reports, 6 9 11 14 16 17 4 retrospective case series, 4 7 8 12 2 letters to the editor, 10 15 and 2 original articles 13 18 ( Table 2 ). 4 6 7 8 9 10 11 12 13 14 15 16 17 18 Overall, 28 cases of DH after LR have been described (excluding our 3 cases). The most common indication of LR were as follows: living donor liver procurement in 11 cases (39.4%), liver metastases in 6 cases (21.4%), HCC in 2 cases (7.1%), adenoma in 2 cases (7.1%), focal nodular hyperplasia in one case (3.6%), and others in 6 cases (21.4%).…”
Section: Resultsmentioning
confidence: 99%
“…In our experience, this complication was not associated with mortality. However, in the literature review ( Table 1 ), 4 6 7 8 9 10 11 12 13 14 15 16 17 18 one patient died 3 months after hepatectomy, secondary to sepsis from a segment of small bowel that perforated into the DH. 13 This suggests that even though this complication is rare, it should be repaired surgically, even for asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect may enlarge progressively, resulting from the constant diaphragmatic motion or the adhesions that form after surgery, with the inflamed postoperative scar tissue exerting traction on the diaphragm [ 6 ]. In addition, Scott et al reported right hepatectomy for liver transplantation to carry the greatest risk for DH because of the right diaphragmatic attachments to the liver, which cover a relatively large surface area and are substantially more adherent than on the left side of the diaphragm and, therefore, increase the risk of inadvertent injury during liver mobilization [ 7 ]. The patient in our case report had undergone hepatectomy with a diaphragm incision and intra-operative direct repair, and then the defect of the DH was observed to be clearly separated from the suture area during the first laparotomy performed.…”
Section: Discussionmentioning
confidence: 99%
“…As CT scan is a part of most cancer follow-up examinations and at the same time the most effective procedure, it should take center stage in routine diagnostics, while sonography, being even easier to perform, could be used as first-line in an emergency situation or in outpatient clinic consultations by experienced examiners [ 23 ]. Although in synopsis of the studies it is shown that the sensitivity of chest X-ray (CXR) for diaphragmatic injuries varies between 40% and 81%, with some studies also speaking of an error rate of 40%, in our opinion, CXR is not a meaningful method, while ultrasound is superior, being proven in several studies as a reliable method of diagnosing diaphragmatic hernias [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%